تكييف النهج التواصلي ــ وضع سياق تدريس اللغة للمتعلمين المتنوعين - Jamoom, Osama Albashir; Al-Omrani, Milood (Al-Qurtas, 2025)
The Communicative Approach (CA) to language teaching has been widely adopted for its focus on real-world communication and its emphasis on developing learners' ability to use language in social contexts. While this approach demonstrates efficacy in diverse settings, its implementation contends with context-specific challenges. This article explores the role of the CA in modern language teaching. It argues that although it provides valuable principles for fostering communicative competence, it should not be treated as a rigid, one-size-fits-all methodology. This article advocates for a more flexible, adaptive approach to language teaching, one that takes into account the diverse needs, cultural contexts, and motivations of learners. Drawing on examples from various educational settings, including those in Vietnam and Chine, the article examines the limitations of the CA when it is applied universally without consideration of local factors. It suggests that teachers should approach the CA as a guiding framework rather than a prescriptive method, integrating it with other teaching strategies as needed. Ultimately, the article calls for a more nuanced understanding of the CA, one that allows for adaptation and customization to meet the unique needs of different learner populations.